(untitled) (Международный научный журнал «Инженер», 2026)
This article presents the procedures and methods for conducting experimental work in determining the laws of interaction of soils with a physical model working body in a laboratory setting. In particular, devices consisting of a physical model, a soil corridor and a movable trolley valets are given, which are used in conducting experimental work. An explanation has also been cited for the clay grunts used to carry out experimental work. In particular, the values the moisture intervals of the soils , compaction coefficients, indicators of the number of plasticity are shown in the table. An expression that determines the moisture content of the soil has been cited. Graphs are constructed showing the relationship of parameters interconnected by the soils moisture feedback. In particular, when the values of the compaction coefficients differ, the internal friction angle of the soils and the state of moisture dependence of the tensile force magnitudes are expressed, as well as the description of the physical model used in the experiment and the physical mechanical properties of the soils used are also given.